VISUALISASI PROSES PEMBUATAN MOBIL MERCEDEZ-BENZ 300SL GULLWING DI TUKSEDO STUDIO DALAM FOTOGRAFI DOKUMENTER - I Kadek Budi Antara; I Wayan Mudana; I Made Saryana (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
The process of making classic cars is certainly an activity that is rarely encountered by the general public and is very interesting to be documented both for the benefit of the company and published for the general public. The process of making a car that is made manually so it takes quite a long time and and goes through quite interesting stages, so it needs to be captured in more detail. To visualize the process of making the Mercedes Benz 300 SL Gullwing car in documentary photography at Tuxedo Studio, it is a unique and lively work. The making of the Mercedes Benz 300 SL Gullwing at Tuksedo Studio became a place and reference for expressing ideas in making documentary photos. In creating this documentary photography, the EDFAT method was applied.The purpose of implementing EDFAT is to describe aspects that need to be considered in shooting in order to obtain comprehensive, varied photos, both from a photographic point of view and in terms of exposure to events or events. Also by going through several stages of the creative process, namely exploration, experimentation, and embodiment. These methods and stages were passed in order to obtain a visual work that was in accordance with the wishes, the stages of the creation process that had been passed, in the end being able to provide a presentation on how to visualize the process of making a Mercedes Benz 300SL Gullwing car in documentary photography.